IDEOLOGICAL FORMATION IN RONDA DRAMA TEXT BY ATUT ADI BASKORO: ANTONIO GRAMSCI PERSPECTIVE (FORMASI IDEOLOGI DALAM TEKS DRAMA RONDA KARYA ATUT ADI BASKORO: PERSPEKTIF ANTONIO GRAMSCI) - Turmudzi, Muhammad Imam (Jurnal Gramatika, 2019)
This study aims to describe ideological formation and ideological negotiations in the drama text "Ronda" by Atut Adi Baskoro. With the focus of the problem raised in this study is the study of drama text by describing ideological formation and ideological negotiations in order to find the use of dominant group ideology and its impact on subaltern groups so that dominant ideologies and negotiated ideologies can be known. The ideological concept in this study uses a literary sociology approach initiated by Antonio Gramsci. The method used is descriptive quality. Data analysis techniques use content analysis techniques. The results of the study indicate the existence of ideological formation in the text, namely from the dominant group adhering to the ideology of fascism and anarchism which dominates the subaltern group of adherents of ideological mysticism. In the text also found the new common sense of the dominant and subaltern groups after ideological negotiations between the dominant and subaltern groups. The new common sense is in the form of a humanist ideology that prioritizes human values and position and makes it a criterion in all things.